Comunanze urbane Autogestione e cura dei luoghi - Belingardi, Chiara Franca Maria (Premio Tesi di Dottorato, 2015)
The volume explores the category of urban spaces that are self-managed by the inhabitants and can be recognized as common goods: urban communities. These are defined as third spaces (neither public nor private) and recognized on the basis of seven characteristics. Furthermore, some proposals are made on how planning can adequately treat these places, through the comparison with some municipal policies and on the basis of the self-determination of experiences in order to build a city really in the hands of its inhabitants. In fact, urban communities can be seen as a strategic place for testing new relationships between citizens and between them and institutions.